GREAT EARTHQUAKES AND SLAB PULL: INTERACTION BETWEEN SEISMIC COUPLING AND PLATE-SLAB COUPLING - Conrad C.P.; Bilek S.; Lithgow-Bertelloni C. (My University, 2004)
Great earthquakes, the few largest earthquakes that account for most of the Earth's seismic energy release, have occurred at only a few subduction zones around the world. Strong locking, or 'seismic coupling', of the interface between plates at certain subduction zones is often invoked to explain these great earthquakes. Although past studies have correlated strong seismic coupling with a compressional stress environment that is characterized by back-arc compression and caused by trenchward motion of the overriding plate, the consequences of this compressional environment for the tectonic forces that drive global plate motions are not yet clear. To examine these consequences, we compared subduction zone earthquake magnitudes to tectonically constrained estimates of the degree to which each slab transmits its excess weight as a direct pull force on a subducting plate. At seismically uncoupled subduction zones that generate only moderate-sized earthquakes, we find that slabs must transmit nearly their entire upper mantle weight as a pull force on the subducting plate. At seismically coupled subduction zones that produce great earthquakes, however, we find that slabs must be nearly completely detached from their subducting plates. This suggests that slabs subducting in a compressional environment experience stress-induced weakening that prevents the effective transmission of the slab pull force. Convergent mantle flow above a descending slab that becomes decoupled from its surface plate may induce additional surface compression that further locks the subduction zone and leads to additional slab decoupling and detachment. The resulting redistribution of plate-driving forces may be responsible for rapid changes in plate motion.
Keywords: SUBDUCTION; SEISMIC COUPLING; TECTONIC PLATE MOTIONS; GREAT EARTHQUAKES; BACK-ARC STRESSES; PLATE-DRIVING MOTIONS; SLAB PULL